Virtual environments for corporate education : employee learning and solutions - Ritke-Jones, William, 1958- (Hershey, PA : Business Science Reference, 2010)
'This book should be used by human resource managers, corporate educators, instructional designers, consultants and researchers who want to discover how people use virtual realities for corporate education'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Virtual reality in management; Employees -- Training of; Virtual reality in education